2018
DOI: 10.18332/tid/99541
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal treatment for smoking cessation with varenicline in alcoholic, methadone-maintained, and psychotic patients: A one-year follow-up

Abstract: INTRODUCTION Numerous studies have evaluated the efficacy and safety of varenicline for smoking cessation in smokers in the general population and, to a lesser extent, among the psychiatric population. However, few studies have evaluated varenicline in patients with other addictions. The present study was conducted to assess outcomes of a multimodal treatment for smoking cessation intervention with varenicline in a sample of alcohol and substance use disorders and patients with psychotic disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…In fact, all studies reported higher biochemically validated smoking reduction rates after treatment, and this effect was maintained at follow-ups in most of them. This conclusion is supported by other studies that also reported the effectiveness of multimodal smoking cessation treatments among patients with stable psychotic disorders (Raich et al, 2018;Stubbs et al, 2015). However, multimodal interventions were not as effective in helping individuals to achieve smoking abstinence and to maintain it over time.…”
Section: Discussionsupporting
confidence: 66%
“…In fact, all studies reported higher biochemically validated smoking reduction rates after treatment, and this effect was maintained at follow-ups in most of them. This conclusion is supported by other studies that also reported the effectiveness of multimodal smoking cessation treatments among patients with stable psychotic disorders (Raich et al, 2018;Stubbs et al, 2015). However, multimodal interventions were not as effective in helping individuals to achieve smoking abstinence and to maintain it over time.…”
Section: Discussionsupporting
confidence: 66%
“…Also, in relapses, no significant difference was found between the two drugs. There are studies showing the superiority of varenicline to bupropion, nicotine replacement therapy and placebo in smoking cessation 8,[27][28][29][30][31][32][33][34][35][36][37] . There are also studies showing that there is no difference in the success of smoking cessation among medical treatments 14 .…”
mentioning
confidence: 99%
“…This finding underscores the potential advantage of directly observed therapy in improving medication adherence, particularly in the initial six weeks of treatment. The findings from Raich et al 19 highlight the necessity for multimodal approaches in treating nicotine dependence in patients with concurrent disorders. The varied patient profiles in this study reinforce the need for personalized treatment plans, considering the unique challenges these individuals face.…”
Section: Discussionmentioning
confidence: 99%